Mechanical properties of short and continuous kenaf/PET fibre reinforced polyoxymethylene composite - Dan-Mallam, Y. (Adcotec Ltd., 2015)
The challenges of improving the mechanical properties of natural fibre composites cannot be over emphasized due to fibre geometry, poor fiber distribution in the matrix, the hydrophilic nature of natural fibers and poor fibre-matrix interfacial adhesion. The primary objective of this research is to study the influence of fibre length on mechanical properties of kenaf/PET fibre reinforced POM and to study the effect of hybridization on mechanical properties of the composites. The composites were produced by compression molding and subsequently subjected to tensile, flexural and impact tests according to their respective ASTM standards. The tensile strength of short POM/kenaf/PET (80/10/10) hybrid composite dropped by approximately 33 from 61.8 MPa to 41.3 MPa compared to neat POM. However, the tensile strength of continuous POM/kenaf composites increased significantly by approximately 127 and 107 for 70/30 and 80/20 compositions compared to neat POM. The flexural moduli of short POM/kenaf/PET (70/15/15) hybrid composite and continuous POM/kenaf (70/30) composite improved by approximately 41 and 29, respectively. The impact strength substantially increased by nearly 161 in continuous POM/kenaf/PET (70/15/15) hybrid composite and 30 in POM/kenaf (80/20) composite. The results show that tensile, flexural and impact properties of the continuous POM/kenaf composites are superior to the short fiber composites, and the influence of hybridization, made a positive impact by enhancing the flexural and impact properties of the composites.